DISTINCTIVE FEATURES OF TOXIC INTESTINAL DISORDERS IN INFANTS AND TODDLERS (International journal of medical sciences, 2025)
Empirical observations indicate that the conventional approaches to diagnosing and managing intestinal toxic disorders in pediatric patients require certain contextual adaptations when implemented in regions with elevated ambient temperatures. These adjustments primarily relate to the nuances of rehydration therapy and to several organizational components of medical care. The latter hold particular relevance, as the concurrence of a hot climate with intestinal infections and specific demographic and social factors such as elevated birth rates, a high proportion of children within the population structure, and the predominance of rural residency among them creates the need for tailored recommendations aimed at both clinical practitioners and administrators of pediatric healthcare systems.